Dampak Implementasi Doa Syafaat Rasul Paulus Menurut Efesus 3:14-21 bagi Pertumbuhan Spiritual Jemaat Tuhan Masa Kini - Baskoro, Paulus Kuntoro; Lestari, Teresia Puji (ICHTUS: Jurnal Teologi dan Pendidikan Kristiani, 2022)
Abstract: Believers who have received salvation in Christ mean they have entered the family of God’sKingdom. As members of God’s Kingdom family, believers must pray for one another. The purposeof this prayer is for the progress or spiritual growth of God’s church, which in this case is God’schurch. Because often, many believers consider it not too important to live in prayer and pray for oneanother. The Apostle Paul in the letter of Ephesians, has set an example of how he intercedes for thecongregation. The content of the apostle Paul’s prayer was that the believers in Ephesus would gainstrength in spiritual warfare, which would impact the extraordinary spiritual growth of the Ephesiancongregation. Therefore, the apostle Paul’s intercessory prayer needs to be implemented in the livesof today’s believers, both in prayer for themselves and His Church, which will bring spiritual growthfor themselves and God’s congregation today. The method used in this research is a descriptivequalitative method that examines the meaning of the impact of intercessory prayer on the spiritualgrowth of God’s congregation. So that God’s congregation can remain strong in facing all lifechallenges and mature spiritually.Keywords: intercessory, prayer, paul, spiritual growth, Ephesus, congregationAbstrak: Orang percaya yang telah beroleh keselamatan dalam Kristus berarti telah masuk dalamkeluarga Kerajaan Allah. Sebagai anggota dari keluarga Kerajaan Allah, orang percaya memilikikewajiban untuk saling mendoakan. Tujuan dari doa ini adalah demi kemajuan ataupunpertumbuhan spiritual jemaat Tuhan yang dalam hal ini adalah gereja Tuhan. Sebab seringkalibanyak orang percaya menganggap tidak terlalu penting hidup dalam doa dan saling mendoakan.Rasul Paulus dalam surat Efesus telah memberi teladan bagaimana ia berdoa syafaat untuk jemaatitu. Isi dari doa rasul Paulus itu ialah supaya orang percaya di Efesus beroleh kekuatan dalampeperangan rohani, yang membawa dampak bagi pertumbuhan spiritual yang luar biasa dari jemaatEfesus. Oleh karena itu, doa syafaat rasul Paulus ini perlu diimplementasikan dalam kehidupanorang percaya masa kini, baik itu dalam doa untuk diri sendiri maupun untuk gereja-Nya, yang akanmembawa pertumbuhan spiritual bagi diri sendiri maupun jemaat Tuhan masa kini. Metode yangdigunakan dalam penelitian ini adalah metode kualitatif deskriptif dengan mengkaji makna dampakdoa safaat bagi pertumbuhan rohani jemaat Tuhan. Sehingga jemaat Tuhan bisa tetap kuatmenghadapi segala tantangan kehidupan serta menjadi dewasa dalam kerohanian.Kata kunci: doa syafaat, paulus, pertumbuhan spiritual, Efesus, jemaat